Effect of thermal modification on the physical properties of juvenile and mature woods of Eucalyptus grandis - Calonego, Fred Willians [UNESP]; Severo, Elias Taylor Durgante [UNESP]; Latorraca, João Vicente (Universidade Federal Rural do Rio de Janeiro, Instituto de Florestas, 2014)
This study aimed to evaluate the effect of thermal treatment on the physical properties of juvenile and mature woods of Eucalyptus grandis. Boards were taken from 30-year-old E. grandis trees. The boards were thermally modified at 180 °C in the Laboratory of Wood Drying and Preservation at UNESP, Botucatu, Sao Paulo state, Brazil. The results showed that thermal modification caused: (1) decrease of 6.8% in the density at 0% equilibrium moisture content of mature wood; (2) significant decreases of 14.7% and 35.6% in the maximum volumetric swellings of juvenile and mature woods, respectively; (3) significant decreases of 13.7% and 21.3% in the equilibrium moisture content of juvenile and mature woods, respectively. The influence of thermal modification in juvenile wood was lower than in mature wood and caused greater uniformity in the physical variations between these types of wood in E. grandis.

Este estudo teve como objetivo avaliar o efeito do tratamento de modificação térmica nas propriedades físicas dos lenhos juvenil e adulto da madeira de Eucalyptus grandis. Para tanto, tábuas centrais foram obtidas de árvores de E. grandis com 30 anos de idade. Esse material foi modificado termicamente a 180 °C no Laboratório de Secagem e Preservação de Madeiras da UNESP, Botucatu-SP, Brasil. Os resultados mostraram que o tratamento de modificação térmica ocasionou: (1) decréscimo de 6,8% na densidade a 0% de umidade no lenho adulto; (2) redução significativa de 14,7% e 35,6% nos inchamentos volumétricos máximos dos lenhos juvenil e adulto, respectivamente; (3) diminuição significativa de 13,7% e 21,3% no teor de umidade de equilíbrio dos lenhos juvenil e adulto, respectivamente. A influência da modificação térmica no lenho juvenil foi menor do que no lenho adulto e ocasionou uma maior uniformização nas propriedades físicas entre esses dois tipos de lenho da madeira de E. grandis.
Efeito da termorretificação nas propriedades físicas dos lenhos juvenil e adulto de Eucalyptus grandis
Keywords: madeira modificada termicamente; eucalipto; inchamentos máximos; densidade da madeira; thermally-modified wood; eucalyptus; maximum swellings; wood density